Self-Reported Sleeping Time Effects on Physical Performance and Body Composition Among Spanish Older Adults: EXERNET-Elder 3.0 study. (September 2022) - Gesteiro, Eva; Aparicio-Ugarriza, Raquel; García-Centeno, María del Carmen; Escobar-Toledo, David; Mañas, Asier; Pérez-Gómez, Jorge; Gusi, Narcís; Gómez-Cabello, Alba; Ara, Ignacio; Casajús, Jose A.; Vicente-Rodríguez, Germán; González-Gross, Marcela
Objective: To determine the link between physical fitness and body composition with nocturnal and nap time in Spanish older adults.Methods: Eight hundred thirty older adults underwent several tests. Sleep was measured using Jenkins Sleep Scale. Nocturnal sleep was categorized (<7, 7–9, and >9 hours), and nap time (no nap, 1–30 minutes, and >30 minutes).Physical fitness was evaluated using validated tests, and body composition by electric bioimpedance.Results: 75.1% of participants were female, mean age 77.7 ± 5.1 years. Mean nocturnal sleep and nap time was 6.7 hours and 23.3 minutes, respectively. Models showed nocturnal sleep >9 hours was significant and positively associated with body shape index (Odds ratio[ OR ] = 4.07 ( p  = .011)) and waist circumference OR  = 1.04 ( p  = .024) in females. Males' waist and hip circumference were positively significantly related to nap time between 1 and 30 minutes, OR  = 1.08, p  = .009 and OR  = 1.08, p  = .048, respectively. In females, nap time >30 minutes was associated with greater fat mass and body shape index OR  = 1.22, p  = .032 and OR  = 3.95, p  = .027, respectively. Physical fitness showed no associations with sleep outcomes.Conclusions: Sleep patterns do not influence physical fitness but body composition, being more related to female body composition as nocturnal and nap sleep were associated with higher fat mass, waist circumference and body shape index, while only short nap times were related to higher waist and hip circumference in males.